Shrine dedicated to Guanyin - Mumbai Archive Project Team (Jio Institute, 2024)
On the ground floor, a shrine is dedicated to Guanyin, the Bodhisattva of mercy and compassion. Red lanterns, symbolizing good fortune and happiness, are commonly hung around the temple, especially during festivals. Murals and paintings depicting scenes from religious texts and mythology enhance the spiritual ambiance of the temple.